PENERAPAN LEARNING CYCLE APPROACH SEBAGAI UPAYA MEMINIMALISASI MISKONSEPSI MAHASISWA PADA MATERI STRUKTUR MOLEKUL - Sumarni, Woro (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), Universitas Negeri Semarang, 2010)
This study aims to diagnose the misconceptions on the molecular structure of matter and investigate the use of learning cycle approach to minimize misconceptions of students on such materials. This research was conducted on students of chemistry education Prodi in one of LPTK in semester one academic year 2009/2010. Data collection techniques used are claim forms diagnostic tests misconception right/ wrong reason given before and after lessons, interviews, and document analysis. The collected data were analyzed using descriptive analysis by way of analyzing the peritem about to be concluded. Results showed that happened on student misconceptions contained in the concept drawing Lewis structures, the determination of polar and non polar, the determination of the geometrical structure based on VSEPR theory and the theory hibrisasi, distinguish between the geometrical structure of the molecular shape, determine the electron configuration for the molecule, and calculate the bond order (b) Frequency of students who have misconceptions have been reduced after being given the study by Learning Cycle approach. Keywords: learning cycle, misconceptions, pembelajaran struktur molekul